Diagnostic accuracy of PET/CT scan in evaluation of clinically suspected recurrent ovarian cancer (Journal of Fatima Jinnah Medical University, 2021)
Background: Accurate evaluation of ovarian carcinoma is utmost important for effective management. PET/CT is reported to be effective in evaluation of suspected recurrence of ovarian carcinoma. This study aims to assess the accuracy of PET/CT in evaluation of recurrent ovarian cancer among clinically suspected cases with rising tumor marker or suspicious clinic-radiological findings.Patients and methods: This prospective cross-sectional study was conducted at Radiology department of Jinnah Postgraduate Medical Centre Karachi from 22nd April 2019 to 21st April 2020. Patients having age of 40 to 60 years and referred for PET scan with suspected recurrence of ovarian carcinoma were consecutively enrolled. Patients were suspected due to relevant history, clinical findings and initial imaging investigations with elevated CA-125 level. Results of 18FDG PET/CT scan was correlated with the raised tumor findings. The PET/CT scan showing abnormally elevated FDG take-up and higher SUV values than the background activity considered recurrence. Diagnostic accuracy of PET/CT was calculated taking raised tumor level as reference category.Results: Of 65 patients, median age was 50 (43-56) years. The findings showed positive cases in 57 (87.7%) while negative in 8 (12.3%) patients, whereas the findings of tumor marker showed raised tumor marker in 61 (93.8%) patients. Diagnostic accuracy of PET/CT showed sensitivity, specificity, positive predicted value, negative predated value, and overall diagnostic accuracy as 93.44%, 100%, 100%, 50%, and 93.85% respectively.Conclusion: A higher accuracy of PET/CT was observed in the diagnosis of recurrent ovarian cancer among clinically suspected cases, thus helping in devising an appropriate management plan by the treating physician.
Keywords: Diagnostic accuracy; PET/CT; Recurrent ovarian cancer